Irrational expectations and econometric practice: discussion of Orphanides and Williams, "Inflation scares and forecast-based monetary policy" - Peter N. Ireland (Federal Reserve Bank of Atlanta, 2003)
Athanasios Orphanides and John C. Williams' excellent conference paper, "Inflation Scares and Forecast-Based Monetary Policy," contributes importantly to the new and rapidly growing branch of the literature on bounded rationality and learning in macroeconomics. Their paper, like many others, derives interesting and useful theoretical results that show how the introduction of bounded rationality and learning impacts on the effects of monetary policy shocks and the characteristics of optimal monetary policy rules. This note suggests that some additional empirical work-some "irrational expectations econometrics," if you will-might serve to make these purely theoretical results seem more relevant and convincing.
Keywords: 330; Equilibrium (Economics); Monetary policy; Macroeconomics; Inflation (Finance); Forecasting